Peningkatan Penyesuaian Diri Remaja Panti Asuhan melalui Pelatihan Regulasi Emosi - Fikri Yumna Aqila; Nanik Prihartanti; Setia Asyanti (Psympathic : Jurnal Ilmiah Psikologi, 2021)
This study ains to examine the effectiveness of emotion regulation training to increase self adjustment. The research method used experiment with pretest posttest control group design. The participants were 20 young orphans, grouped into experimental and control group with 10 participants for each group obtained through matching method. The participants were given pretest, posttest, and follow up using self adjustment scale reviewed by expert judgment. The Mann Whitney U Test shows that there are significant differences on self adjustment between experimental and control group. The Wilcoxon test shows that there is a significant increase of self adjustment score on experimental group after the training was given. Thus, the emotion regulation training was effective to improve youth's self adjustment who live in the orphanage.